2013
DOI: 10.1103/physrevb.87.224420
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation and the Elliott-Yafet parameter in W(001) ultrathin films: Surface states, anisotropy, and oscillation effects

Abstract: Using first-principles methods based on density-functional theory, we investigate the spin relaxation in W(001) ultrathin films. Within the framework of the Elliott-Yafet theory, we calculate the spin mixing of the Bloch states and we explicitly consider spin-flip scattering off self-adatoms. At small film thicknesses, we find an oscillatory behavior of the spin-mixing parameter and relaxation rate as a function of the film thickness, which we trace back to surface-state properties. We also analyze the Rashba … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 49 publications
(70 reference statements)
3
19
0
Order By: Relevance
“…For one thing we found 30 that the free-electron-like Fermi surface of the noble metals, when projected in the surface Brillouin zone of the ultrathin film, cuts through the Brillouin zone edge producing spin-flip hot spots that have only been reported in the case of multivalent metals 18 so far. Additionally we analyzed the surface states in the case of W(001) films 29 and found that the Rashba character can strongly contribute to spin relaxation; we also saw an oscillatory behavior of the spin relaxation as a function of the film thickness. In both cases 29,30 we also found a considerable anisotropy of the EYP as well as spin-relaxation rate with respect to the angle between the injected spin polarization and the film normal.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For one thing we found 30 that the free-electron-like Fermi surface of the noble metals, when projected in the surface Brillouin zone of the ultrathin film, cuts through the Brillouin zone edge producing spin-flip hot spots that have only been reported in the case of multivalent metals 18 so far. Additionally we analyzed the surface states in the case of W(001) films 29 and found that the Rashba character can strongly contribute to spin relaxation; we also saw an oscillatory behavior of the spin relaxation as a function of the film thickness. In both cases 29,30 we also found a considerable anisotropy of the EYP as well as spin-relaxation rate with respect to the angle between the injected spin polarization and the film normal.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally we analyzed the surface states in the case of W(001) films 29 and found that the Rashba character can strongly contribute to spin relaxation; we also saw an oscillatory behavior of the spin relaxation as a function of the film thickness. In both cases 29,30 we also found a considerable anisotropy of the EYP as well as spin-relaxation rate with respect to the angle between the injected spin polarization and the film normal.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations